Fuzzy inventory models with partial backordering for deteriorating items under stochastic inflationary conditions: Comparative comparison of the modeling methods. Issue 1 (1st January 2019) - Fathalizadeh, Shabnam; Mirzazadeh, Abolfazl; Ghodratnama, Ali
Abstract: This article presents two deteriorating inventory models with constant demand and deterioration rates to determine optimal ordering policy under inflation and partial backlogging with respect to two modeling methods, the average annual cost method and the discounted cost method. Minimizing the total inventory costs over an infinite time horizon is the objective function of the models. Here, the unit purchasing cost is in the uncertain environment and assumed as a fuzzy number. The fuzzy models are solved by the fuzzy non-linear programming method with a numerical example in the GAMS software. The two mentioned modeling methods have been compared to each other in this study. The obtained results of this comparison will be useful for the inventory managers to make a better decision. A sensitivity analysis of the wide range of the problem parameters of the derived models to illustrate the theoretical results.